Ta’thīr Taṭbīq Ṭarīqah al-Ghina’ fī Tarqiyah Istīʿāb al-Mufradāt al-‘Arabiyah - Silvia Fauziah; Al Baihaqi Anas (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The problem in this research that students are less enthusiastic about learning Arabic, and teachers do not use good and interesting learning methods. Teachers do not use modern methods, but only use books, boards and pens. So the students got bored and students' motivation in learning Arabic is low. The research aims to the application of the singing method affects the promotion of vocabulary proficiency among fifth-grade students in the public elementary school 1 Agam. The method used by the researcher is the descriptive quantitative research method. It is the use of statistical formulas that correspond to existing problems. Meanwhile, to find out the effect of applying the singing method on students’ vocabulary pick-up in public elementary school 1 Agam, the researcher used a t-test formula at 1% and 5% levels. It means at 40 df 1% level = 2.423 and 5% level = 2.021. Because of the significance level of the calculation t compared to the table t, the null hypothesis is rejected and the alternative hypothesis is accepted, so the conclusion is that there is an effect of applying the singing method in vocabulary picking for fifth-grade students in public elementary school 1 Agam. المشكلات في هذا البحث لم يستخدم المعلمة الطريقة الحديثة، ولكن يستخدم الكتاب، والسبورة، والقلم فقط، دافع الطلاب في تعليم اللغة العربية منخفض. قدرة الطلاب في تعلم اللغة العربية منخفض. حتى يشعر الطلاب بالملل ويقل دافع الطلاب لتعلم اللغة العربية. تهدف هذه الدراسة إلى تحديد تأثير تطبيق أسلوب الغناء على زيادة إتقان المفردات لدى طلاب الصف الخامس في المدرسة الابتدائية العامة 1 آغام. المنهج الذي تستخدمه الباحثة في هذا البحث هو منهج البحث الكمي الوصفي. وهو استخدام الصيغ الإحصائية التي تتوافق مع المشكلات القائمة. وفي الوقت نفسه، لمعرفة تأثير تطبيق طريقة الغناء في إتقان الطلاب المفردات في المدرسة الابتدائية العامة 1 آغام، استخدمت الباحثة صيغة اختبار t عند مستويات 1٪ و 5٪. يعني ذلك عند 40 df مستوى 1٪ = 2.423 ومستوى 5٪ = 2.021. بسبب مستوى دلالة الحساب t مقارنة بالجدول t، يتم رفض فرض الفرضية الصفرية ويتم قبول الفرضية البديلة، وبالتالي فإن الاستنتاج هو أن هناك تأثيراً لتطبيق طريقة الغناء في إتقان الطلاب المفردات. فنتيجة البحث أن الفرضية الصفرية (Ho) مردودة والفرضية البدلية (Ha)مقبولة. أن يوجد الفرق بين الفصلين دل فرق حقيقي بعد استعمال طريقة الغناء في تعليم المفردات لطلاب الفصل الخامس.